ANALISIS STRATEGI PENGELOLAAN KOLEKSI JOGJA LIBRARY CENTER DALAM MENGHADAPI MASYARAKAT INFORMASI - Mubarokah, Adzkiyah; Rodin, Rhoni (UPT Perpustakaan Universitas Bengkulu, 2023)
ABSTRACT Analysis of Jogja Library Center's Collection Management Strategy in Dealing with the Information Society aims to review what strategies must be used in order to continue to grow in the era of the information society. This research uses qualitative methods with a descriptive approach through field research methods. Research data were obtained from interviews with informants, literature reviews, and documentation. This study found that the Jogja Library Center collection management strategy owned by the DPAD DIY Library Service Center was able to adapt by utilizing technology. This study was reviewed with SOSTAC theory (Situation Analysis, Objectives, Strategy, Tactics, Actions, Control). The results of the research show that Jogja Library Center has subscribed to electronic collections while also continuing to subscribe to printed collections. Jogja Library Center has also digitized the collection of old newspapers and magazines whose physical condition is no longer possible to be read directly by users. Jogja Library Center also conducts various collection collaborations in order to be able to meet the needs of the information community. Keywords: Strategy Analysis, Collection Management, Information Society.